2012
DOI: 10.3233/jad-2012-121093
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of TBS-Extractable Hyperphosphorylated Tau Species: Aggregation Intermediates in rTg4510 Mouse Brain

Abstract: Conditional overexpression of four-repeat human tau containing the P301L missense mutation in the rTg4510 mouse model of tauopathy leads to progressive accumulation of neurofibrillary tangles and hyperphosphorylated, sarkosyl-insoluble tau species, which are biochemically comparable to abnormal tau characteristic of hereditary tauopathies termed FTDP-17. To fully understand the impact of tau species at different stages of self-assembly on neurodegeneration, we fractionated rTg4510 brain representing several st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 41 publications
7
83
0
Order By: Relevance
“…Abnormal elevations in tau phosphorylation at the PHF-1, CP-13 and AT-8 epitopes initially affected endogenous murine Tau, most prominently at the major 50 kDa species, but by 12 months of age progressed to encompass all remaining isoforms. Despite the elevation in tau phosphorylation there was no notable shift in electrophoretic migration nor the emergence of specific hyperphosphorylated species as reported in human AD cases (Flament and Delacourte, 1989) and in several FTD Tau mouse models (Berger et al, 2007;Sahara et al, 2013). The evidence present here suggests that elevations in tau phosphorylation may be sufficient to driving quantifiable behavioural phenotypes.…”
Section: Transgene Expression and Protein Profilessupporting
confidence: 46%
“…Abnormal elevations in tau phosphorylation at the PHF-1, CP-13 and AT-8 epitopes initially affected endogenous murine Tau, most prominently at the major 50 kDa species, but by 12 months of age progressed to encompass all remaining isoforms. Despite the elevation in tau phosphorylation there was no notable shift in electrophoretic migration nor the emergence of specific hyperphosphorylated species as reported in human AD cases (Flament and Delacourte, 1989) and in several FTD Tau mouse models (Berger et al, 2007;Sahara et al, 2013). The evidence present here suggests that elevations in tau phosphorylation may be sufficient to driving quantifiable behavioural phenotypes.…”
Section: Transgene Expression and Protein Profilessupporting
confidence: 46%
“…The cerebral cortex and hippocampus (ctx+hip) of the right hemisphere of each animal were quickly frozen on dry ice and stored at −80°C until use. Tissues were then homogenized in 10 volumes of Tris-buffered saline [TBS: 50 mM Tris/HCl (pH 7.4), 274 mM NaCl, 5 mM KCl, 1% protease inhibitor mixture (Sigma, St. Louis, MO), 1% phosphatase inhibitor cocktail I & II (Sigma), and 1 mM phenylmethylsulfonyl fluoride (PMSF)] (Berger et al, 2007; Sahara et al, 2012; Santacruz et al, 2005). The homogenates were centrifuged at 27,000 × g for 20 min at 4°C to obtain supernatant (S1) and pellet fractions.…”
Section: Methodsmentioning
confidence: 99%
“…The injected ALZ17 mice quickly developed solid filamentous tau pathology, and administration of immuno-depleted brain extracts from P301S mice or extracts from wild type mice did not induce tau pathology. Fractionation of the brain extracts in soluble (S1) and sarkosyl insoluble tau (P3) [19] and injection of these into ALZ17 mice demonstrated that the P3 fraction is most competent in inducing pathology. It contains most of the intracellular hyperphosphorylated filamentous tau.…”
mentioning
confidence: 99%